PERAN RELAWAN DEMOKRASI (RELASI) SEBAGAI “ELECTION MARKETER”: (Studi Kasus Pemilihan Umum Legislatif 2014 di Kabupaten Pasuruan) - M. Daimul Abror; Heri Sunarno (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2017)
The voter turnout 3 last period (1999-2009) has decreased significantly. At 1999 92.6% choseen and 7.3% abstains, at 2004 84.1% choseen and 15.9% abstains, at 2009 70.9% choosen and 29.1% abstains. (www.merdeka.com). These conditions encourage KPURI to form Volunteer Democracy (VD) as an agent that helps the socialization of Election 2014. This study aims to comprehensively assess the role of VD as